2012
DOI: 10.1111/j.1365-2052.2012.02365.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci segregating in crosses between New Hampshire and White Leghorn chicken lines: III. Fat deposition and intramuscular fat content

Abstract: In this study, a genome scan was performed to detect genomic loci that affect fat deposition in white adipose tissues and muscles in 278 F (2) males of reciprocal crosses between the genetically and phenotypically extreme inbred chicken lines New Hampshire (NHI) and White Leghorn (WL77). Genome-wide highly significant quantitative trait loci (QTL) influencing fat deposition in white adipose tissues were found on GGA2 and 4. The peak QTL positions for different visceral and subcutaneous white adipose tissues we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…) and fat deposition (mass of white adipose tissues included the mass of adipose tissue around the heart, retroperitoneal, peritoneal, mesenteric, gonadal and subcutaneous) (Nassar et al . ). Body weights of all chickens were recorded at hatch and at 5, 10, 15 and 20 weeks.…”
Section: Qtl For Growth Traits At Different Ages In the Reciprocal F2mentioning
confidence: 97%
See 2 more Smart Citations
“…) and fat deposition (mass of white adipose tissues included the mass of adipose tissue around the heart, retroperitoneal, peritoneal, mesenteric, gonadal and subcutaneous) (Nassar et al . ). Body weights of all chickens were recorded at hatch and at 5, 10, 15 and 20 weeks.…”
Section: Qtl For Growth Traits At Different Ages In the Reciprocal F2mentioning
confidence: 97%
“…; Nassar et al . , ). For QTL mapping, we used the least squares method of Haley & Knott () implemented in the gridqtl program (http://www.gridqtl.org.uk/; Seaton et al .…”
Section: Qtl For Growth Traits At Different Ages In the Reciprocal F2mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, chicken IMF accumulation is dependent on the transport and uptake of blood lipids as well as lipogenesis subsequently in muscle rather than de novo fatty acids synthesis (Griffin et al, 1987). Previous studies have identified about 20 quantitative trait loci (QTL) related to chicken IMF, which are mainly located on chromosomes 1, 2, 5, 23 (Jennen et al, 2005; D'Andre et al, 2010; Ye et al, 2010; Jia et al, 2012; Liu et al, 2013; Nassar et al, 2013; Sun et al, 2013; Zhang T. et al, 2015). Otherwise, a large number of genes including GPAT1, ACC, CD36, AGPAT1 , and DGAT2 (Jeong et al, 2012), FABP (Ye et al, 2010; Serao et al, 2011), LPL (Zhang X. D. et al, 2015), DGAT1 (Li et al, 2013) were recognized as candidate genes for IMF, but their molecular mechanisms affecting IMF are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A maior parte da gordura na carcaça em galinhas está depositada sob pele, nos órgãos e na porção abdominal (NASSAR et al, 2012). Aves com deposição excessiva de gordura podem causar problemas no processamento da carne e também uma rejeição por parte dos consumidores, preocupados com a qualidade nutricional dos cortes ZHOU et al 2007).…”
Section: Deposição De Gordura Na Carcaça: Uma Abordagem Genéticaunclassified